PENGARUH MODAL USAHA TERHADAP PENDAPATAN PEDAGANG SAYUR PASCA PANDEMI VIRUS CORONA DI PASAR TRADISIONAL UNIT II - Muhamad Sarifudin; Ayuningsih Larasti (Journal of Accounting Taxing and Auditing (JATA), 2023)
AbstractTrade is a very important thing in the economic activities of a country. The active trading activity of a country is an indication of the level of prosperity of the people and a benchmark for the level of the country's economy itself. So that it can be said that trade is the lifeblood of a country's economy. However, this has not been the case, since the beginning of 2020 the outbreak of Coronavirus Disease 2019 (COVID-19) has not only attacked the health sector, it has also attacked various sectors of human life in various countries, as if disrupting human life which has an impact on economic activity. According to the Ministry of Health of the Republic of Indonesia, the total confirmed cases of Covid-19 in Indonesia as of February 9 2022 were 4,626,936 people who had tested positive for this virus with deaths reaching 144,784 people. (Faryyanida Putwiliani: Tribunnews.com 9 February 2022). The informal sector is one of the sectors affected by the corona virus. The informal sector is a small business unit with small capital and very simple management. The informal sector is quite dominant in absorbing the workforce, especially in villages. One of the business activities in the informal sector is trade. Most people are interested in trading skills because without special skills or high education they can enter into these activities. Keywords: Business Capital, Income, Vegetable Traders, Corona Virus.  AbstrakPerdagangan merupakan suatu hal yang sangat penting dalam kegiatan perekonomian suatu negara. Giatnya aktivitas perdagang suatu negara menjadi indikasi tingkat kemakmuran masyarakat serta menjadi tolak ukur tingkat perekonomian negara itu sendiri. Sehingga dapat dikatakan perdagangan merupakan urat nadi perekonomian suatu negara. Namun tidak demikian, semenjak awal tahun 2020 mewabahnya Coronavirus Disease 2019 (COVID-19)  bukan hanya menyerang sektor kesehatan juga telah menyerang berbagai sektor kehidupan manusia di berbagai negeri seolah mengacaukan  kehidupan manusia yang berdampak pada aktivitas perekonomian . Menurut Kementerian Kesehatan Republik Indonesia, total kasus konfirmasi Covid-19 di Indonesia per tanggal 9 Februari 2022  sebanyak 4.626.936 orang sudah positif terjangkit virus ini dengan kematian mencapai 144.784 orang.  ( Faryyanida Putwiliani : Tribunnews.com 9 Februari 2022). Sektor informal merupakan salah satu sektor yang terkena imbas adanya virus corona. Sektor informal merupakan unit usaha kecil dengan modal kecil  serta pengelolahanya yang sangat sederhana. Sektor informal cukup dominan dalam menyerap angkatan kerja khususnya di Desa. Salah satu kegiatan usaha di sektor informal yaitu perdagangan. Keahlian berdagang lebih banyak di minati oleh sebagian besar masyarakat karena tanpa keahlian khusus atau pendidikan yang tinggi bisa masuk ke dalam kegiatan tersebut. Kata kunci : Modal Usaha, Pendapatan, Pedagang Sayur, Virus Corona.